The concise Oxford dictionary of earth sciences (Oxford University Press, 1991)
The book offers over clear and up-to-date entries; wide coverage including climatology, economic geography, geochemistry, mineralogy, oceanography, palaeontology, petrology, and volcanology; and biographical notes on important figures in history of the subject.